Development of an easy and rapid analytical method for the extraction and preconcentration of chloroquine phosphate from human biofluids prior to GC?MS analysis - Bodur, Suleyman; Erarpat, Sezin; Gunkara, Omer Tahir; Bakirdere, Sezgin (ELSEVIER SCIENCE INC, 2021)
A vortex assisted spraying based fine droplet formation liquid phase microextraction (VA-SFDF-LPME) method was developed to determine chloroquine phosphate at trace levels in human serum, urine and saliva samples by gas chromatography?mass spectrometry (GC?MS) with single quadrupole mass analyzer. In the first part, several liquid phase microextraction (LPME) and magnetic solid phase extraction (MSPE) methods were compared to each other in order to observe their extraction ability for the analyte. VA-SFDF-LPME method was selected as an efficient and easy extraction method due to its higher extraction efficiency. Optimization studies were carried out for the parameters such as extraction solvent type, sodium hydroxide volume/concentration, sample volume, spraying number and mixing type/period. Tukey?s method based on post hoc test was applied to all experimental data for the selection of optimum values. Optimum extraction parameters were found to be 12 mL initial sample volume, two sprays of dichloromethane, 0.75 mL of 60 g/kg sodium hydroxide and 15 s vortex. Under the optimum conditions, limit of detection and quantification (LOD and LOQ) were calculated as 2.8 and 9.2 ?g/kg, respectively. Detection power of the GC?MS system was increased by approximately 317 folds with the developed extraction/preconcentration method. The applicability and accuracy of the proposed method was evaluated by spiking experiments and percent recovery results for human urine, serum and saliva samples were found in the range of 90.9% and 114.0% with low standard deviation values (1.9?9.4).
Keywords: Biological samples; Chloroquine phosphate; Liquid phase microextraction; Magnetic solid phase extraction; LIQUID-LIQUID MICROEXTRACTION; DRIED BLOOD SPOTS; GAS-CHROMATOGRAPHY; DRUGS; SOLVENT; METABOLITES; URINE; Pharmacology & Pharmacy; Toxicology